Optimasi Variasi Konsentrasi Asam Trikloroasetat dalam Penanganan Sampel Ikterik pada Pemeriksaan Kadar Asam Urat Metode Uricase - Sulthan Abyan Surya Durachman; Ani Riyani; Dhini Annisa Rahmasari Kanto; Dewi Nurhayati (Poltekkes Kemenkes Semarang, 2026)
Uric acid examination of the uricase method can be disturbed due to bilirubin in icteric serum. Bilirubin absorbs light at a similar wavelength to uricase reaction products, so it can cause gout results to appear higher than they actually are. To overcome this, proper pre-analytical handLing is needed with the addition of trichloroacetic acid (TCA). The purpose of this study was to determine the difference in uric acid levels before and after the addition of TCA to icteric serum and to determine the optimal concentration of TCA to reduce bilirubin disorders in uric acid examination. This research method uses a quasi-experiment using pooled sera that were recognized using catfish bile, with bilirubin levels of 2.13; 2.83; and 3.96 mg/dL. Each sample was treated with TCA at concentrations of 4%, 5%, and 6%. Uric acid levels were checked using the uricase method and data were analyzed using ANOVA and Post Hoc tests. The results showed a decrease in uric acid levels as TCA concentrations increased. The concentration of 6% TCA provided the most significant reduction, but the 5% TCA at bilirubin level of 2.83 mg/dL showed no significant difference compared to normal pooled sera (p > 0.05), suggesting that 5% TCA was the optimal concentration in the handLing of icteric samples on uric acid examination.